(untitled) (Педагогіка вищої та середньої школи, 2010)
In the article the essence signs of the artistically expressed national existential type of thesaurus are exposed in a poetry V. Stus, N. Vyngranovskiy, V. Symonenko. The specific of thought is analysed from point of psycholinguistic as deeply national historical understand ing the national existential type of pre-knowledge is outlined in theory to semanentic Ukrainian life .